Security of Quick Response Code - Ravikumar, K; Geetha, R (International Journal of Computer Sciences and Engineering, 2020)
QR (Quick Response) Codes and the way they will be wont to attack each human interaction and automatic systems. Because the encoded data is meant to be code solely, some individuals cannot distinguish between a legitimate and a maliciously manipulated QR code. Whereas humans may fall for phishing attacks, automatic readers square measure possibly susceptible to SQL injections and command injections. Our contribution consists of Associate in Nursing Associate in Nursing lysis of the QR Code as an attack vector, showing totally different attack methods from the attackers purpose of read and exploring their potential consequences.